DEVELOPING A PROTOTYPE OF MOLECULEARN: INTERACTIVE SCAFFOLDING-BASED MEDIA FOR MODERN CHROMATOGRAPHY LEARNING - Faizal Akhmad Adi Masbukhin; Ayu Fahimah Diniyah Wathi; Dona Suciana; Inas Sausan; Sukma Wahyu Wijayanti (Seminar Nasional Pendidikan IPA Ke III Tahun 2025, 2025)
This study presents the development of MolecuLearn, a prototype of interactive learning media based on scaffolding strategies, designed to support students' understanding of modern chromatography in a distance learning. Using the design thinking approach—empathize, define, ideate, prototype, and test—the development process was conducted systematically and collaboratively between researchers, chemistry education lecturers, and IT developers. The initial needs analysis involved 29 chemistry education students at Universitas Terbuka, revealing that 51.16% strongly agreed and 37.21% agreed on the importance of interactive, scaffolded media to support concept mastery. The Define stage highlighted core problems such as the abstract nature of chromatography, limited access to laboratory practice, and students’ need for structured learning guidance. The Ideate stage produced flowcharts, user interface designs, and key features including animated videos, feedback-based quizzes, and simulations—all integrating scaffolding principles to provide stepwise guidance. A web-based prototype of MolecuLearn was then developed with functional backend (course management, user administration, quiz scoring) and frontend (learning dashboard, interactive modules, user registration) components. Validation by three experts (subject, media, language) and limited trials with students confirmed the media’s effectiveness and usability. Key strengths identified were its visual clarity, interactive features, and adaptive learning path. The findings suggest that MolecuLearn is a viable and engaging platform that bridges the gap between theory and practice in chemistry education. Its scaffolding-based design helps students learn independently while still receiving structured support, especially in complex topics like chromatography. The study recommends broader implementation and further development of this platform for other abstract chemistry topics in distance education.